SOM's Computer Group: Narratives of women in early architectural computing. (September 2021) - Doyle, Shelby Elizabeth; Senske, Nick S
Cultural narratives of digital technology in architecture rely heavily upon stories of unique, almost always male, genius and often deny the collective intellectual labor of technology's construction. These narratives are perpetuated by a historical record which does not fully address the contributions of women to the history of digital technology. Because this history is not well-documented, there is an opportunity to represent these events in a manner which is more inclusive and equitable. Toward that end, this article focuses on narratives from the SOM Computing Group (1964–1990), as a means of correcting the historical record and addressing gender equity in the profession. The interviews collected here highlight several women who helped to integrate technologies into architecture through professional experimentation and cross-disciplinary collaboration. While it is not a comprehensive history, this work represents the beginning of an agenda to produce a history of technology in architecture which better reflects the contributions of women to the digital designs of today.